Factors Associated with Poor Therapeutic Compliance Among Diabetic Patients in Health Facilities of Kinshasa - Atantama M; Mafuta Munganga D; Kapongo Yobo R; Bidingija Mabika J; Mikobi Minga JP; Kisoka Lusunsi C; Kasiam Lasi On'Kin JB; Otshudi Onembo N; Bayauli Mwasa P (Diabetes, Metabolic Syndrome and Obesity)
Magloire Atantama,1 Danny Mafuta Munganga,1 Remy Kapongo Yobo,1 Joseph Bidingija Mabika,1 Jeje-Paul Mikobi Minga,1 Christian Kisoka Lusunsi,2 Jean-Bosco Kasiam Lasi On’Kin,1 Noël Otshudi Onembo,2 Pascal Bayauli Mwasa1 1Unit of Endocrinology and Nuclear Medicine, Department of Internal Medicine, Kinshasa University Hospital, Kinshasa, Democratic Republic of the Congo; 2Cardiology Unit, Department of Internal Medicine, Kinshasa University Hospital, Kinshasa, Democratic Republic of the CongoCorrespondence: Magloire Atantama, Unit of Endocrinology and Nuclear Medicine, Department of Internal Medicine, Kinshasa University Hospital, Kinshasa, Democratic Republic of the Congo, Email dratamagloire80@gmail.comBackground: Poor therapeutic compliance among diabetic patients is one of the public health issues contributing to inadequate diabetes mellitus control and an increased risk of chronic complications. This study aimed to determine the frequency and factors associated with poor therapeutic compliance among diabetic patients in Kinshasa.Methods: A cross-sectional study was conducted between November 2021 and November 2022 on diabetic patients aged at least 18 years who visited four health facilities in Kinshasa. The Morisky questionnaire was used to assess therapeutic compliance. Data analysis was carried out using SPSS 26 software. Descriptive analyses, Pearson’s chi-square test, Mann–Whitney U-test, and logistic regression were applied. A p-value < 0.05 was considered statistically significant.Results: A total of 131 participants were enrolled, of which 88 (67.1%) had poor compliance. The mean age was 53.8 ± 16.5 years, with male participants representing 67.9%. Median values of blood glucose, glycated hemoglobin (HbA1c), triglycerides (TG), and LDL-cholesterol were high in the non-compliant group with respectively 147.5 mg/dL, 8.5%, 146.9 mg/dL, and 116.5 mg/dL. Inadequate self-monitoring (AOR: 10.144, 95% CI 3.543– 29.040, p< 0.001), treatment mode combining oral antidiabetic drugs (OADs) and insulin (AOR: 3.098 95% CI 1.078– 8.904, p=0.036) were significantly associated with poor compliance with treatment.Conclusion: The present study revealed a suboptimal level of therapeutic compliance among participants while highlighting associated factors such as treatment type and inadequate self-monitoring. Thus, setting up a team focusing on therapeutic education is required for better disease management.Keywords: non-compliance, diabetes mellitus, Kinshasa